The Impact of Minimum Energy Performance Standards (MEPS) Regulation on Electricity Saving in Malaysia - Salleh S.F.; Roslan M.E.; Mohd Isa A.; Basri Nair M.F.; Salleh S.S. (Institute of Physics Publishing, 2023)
Air conditioning; Commerce; Domestic appliances; Energy conservation; Manufacture; Power quality; Sales; Annual sales; Electrical appliances; Electricity regulations; Electricity saving; Electricity-consumption; Energy use; Malaysians; Minimum energy; Energy efficiency